Participação de idosos em um projeto de educação continuada sob a perspectiva da psicologia social comunitária - Yamasaki, Flávia (2016)
The population aging phenomenon is a global reality and demand attention of society on the issue of elderly´s quality of life. Nowadays, the concept of the elderly as a disabled and invalid individual is already changing because studies indicate that factors such as adequate food, physical activity, mental stimulation, social interaction and positive attitudes can slow or minimize the effects of aging. Due to this reality, it is important to have continuous education programs seeking to improve well-being and quality of life for elderly. Within this context, this study aims to answer the following questions: How people over 55 years understand their participation in a UnATI project and what are the impacts of participation in daily life. From these results it will be possible to understand the meaning for the elderly participants in the Open University of Maturity, identify the main reasons why the elderly seek to study in the UAM, evaluate expectations about the project, analyze whether the knowledge acquired during the project were useful to the lives of participants and know the possible benefits of participation accordingly to the subscribers. This is a qualitative study, cross-sectional, exploratory and descriptive, in the approach to social constructionist perspective of Gergen and Gergen (2010). The survey was conducted with 10 students enrolled in a Project Open University of Maturity of the Universidade Federal do Paraná in 2015, selected by convenience. Semi-structured interviews were used as data collection instrument. The interviews were recorded, transcribed and data were submitted to analysis of the discursive practices of Spink and Medrado (2013). Analyzing the interviews, it was possible to highlight some important issues, such as understanding the own aging process, the reasons that led them to pursue the project, the initial expectations of participants, the acquired knowledge, preferred methodology and also the criticisms and suggestions. These facts lead to believe that despite being an university extension project, there is still lack of professionals with training in the teachinglearning process of the elderly, and there is also the need for attention to the infrastructure and accessibility of these host institutions. The project enables seniors to deal with his issues, providing resources to face the aging process more actively, preventing physical and psychological discomfort. Thus, it is necessary that the society recognizes the potential of these projects to improve the life of these elderly citizens and more so the number of participants can increase